HLA-DO is a negative modulator of HLA-DM-mediated MHC class II peptide loading - van Ham, S M; Tjin, E P; Lillemeier, B F; Grüneberg, U; van Meijgaarden, K E; Pastoors, L; Verwoerd, D; Tulp, A; Canas, B; Rahman, D; Ottenhoff, T H; Pappin, D J; et al. (Current biology, 1997)
Class II molecules of the major histocompatibility complex become loaded with antigenic peptides after dissociation of invariant chainderived peptides (CLIP) from the peptide-binding groove. The human leukocyte antigen (HLA)-DM is a prerequisite for this process, which takes place in specialised intracellular compartments. HLA-DM catalyses the peptide-exchange process, simultaneously functioning as a peptide 'editor', favouring the presentation of stably binding peptides. Recently, HLA-DO, an unconventional class II molecule, has been found associated with HLA-DM in B cells, yet its function has remained elusive. The function of the HLA-DO complex was investigated by expression of both chains of the HLA-DO heterodimer (either alone or fused to green fluorescent protein) in human Mel JuSo cells. Expression of HLA-DO resulted in greatly enhanced surface expression of CLIP via HLA-DR3, the conversion of class II complexes to the SDS-unstable phenotype and reduced antigen presentation to T-cell clones. Analysis of peptides eluted from HLA-DR3 demonstrated that CLIP was the major peptide bound to class II in the HLA-DO transfectants. Peptide exchange assays in vitro revealed that HLA-DO functions directly at the level of class II peptide loading by inhibiting the catalytic action of HLA-DM. HLA-DO is a negative modulator of HLA-DM. By stably associating with HLA-DM, the catalytic action of HLA-DM on class II peptide loading is inhibited. HLA-DO thus affects the peptide repertoire that is eventually presented to the immune system by MHC class II molecules.